Three Distinct Patterns of Histone H3Y41 Phosphorylation Mark Active Genes - Mark A. Dawson; Samuel D. Foster; Andrew J. Bannister; Samuel C. Robson; Rebecca Hannah; Xiaonan Wang; Blerta Xhemalce; Andrew D. Wood; Anthony R. Green; Berthold Göttgens; Tony Kouzarides (Cell Reports, 2012)
The JAK2 tyrosine kinase is a critical mediator of cytokine-induced signaling. It plays a role in the nucleus, where it regulates transcription by phosphorylating histone H3 at tyrosine 41 (H3Y41ph). We used chromatin immunoprecipitation coupled to massively parallel DNA sequencing (ChIP-seq) to define the genome-wide pattern of H3Y41ph in human erythroid leukemia cells. Our results indicate that H3Y41ph is located at three distinct sites: (1) at a subset of active promoters, where it overlaps with H3K4me3, (2) at distal cis-regulatory elements, where it coincides with the binding of STAT5, and (3) throughout the transcribed regions of active, tissue-specific hematopoietic genes. Together, these data extend our understanding of this conserved and essential signaling pathway and provide insight into the mechanisms by which extracellular stimuli may lead to the coordinated regulation of transcription.